Integration of Noble Moral Values in Indonesian Language Learning Materials to Foster Student Language Politeness in Ad-Dimyati Bandung Integrated Vocational School (SMK Terpadu) - Ifah Khadijah (International Journal of Nusantara Islam, 2017)
The importance of learning noble moral values, morals and nobility for all citizens of the nation should not be denied anymore. A country or a nation can collapse because officials and some of their people behave immorally. Immoral behavior will lead to riots, confusion, irregularities and others that cause the destruction of a nation. Therefore, noble moral values need to be taught so that present and future generations are able to behave according to the expected morals This research is a descriptive case study with a qualitative research design. The subjects of this study were students at Ad-Dimyati Integrated Vocational School Bandung. This study uses five data collection techniques, namely: observation, field notes, recording, document review, and interviews. Interrogation of noble moral values on Indonesian language lessons to form students' language skills in the Ad-Dimyati Integrated Vocational School is conducted through learning activities. The implementation of the interrogation of noble moral values on Indonesian language lessons to form students' language skills in Ad-Dimyati Integrated Vocational School is based on the potential, development and condition of students to master competencies that are useful for them. Implementation of the integration of noble moral values on Indonesian language lessons to form student language politeness using a multi-strategic and multi-media approach, adequate learning resources and technology, and utilizing the surrounding environment as a learning resource, in line with the vision of Ad-Dimyati Integrated Vocational School.